2020
DOI: 10.1021/jacs.0c10924
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling Two Pathways for Electrochemical Alcohol and Aldehyde Oxidation on NiOOH

Abstract: Selective oxidation of alcohols to their corresponding aldehyde or carboxylic acid is one of the most important classes of organic synthesis reactions. In addition, electrochemical alcohol oxidation is considered a viable anode reaction that can be paired with H 2 evolution or other reductive fuel production reactions in electrochemical and photoelectrochemical cells. NiOOH, a material that has been extensively studied as an oxygen evolution catalyst, is among the most promising electrocatalysts for selective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
245
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 198 publications
(290 citation statements)
references
References 38 publications
(89 reference statements)
18
245
0
Order By: Relevance
“…While in the case of Co 4+ , the oxidation current quickly increases after the onset of Co 4+ formation, suggesting the consumption rate of Co 4+ well surpasses its generation rate and therefore increasing quantity of M 4+ is generated and participating in the HMF oxidation. Based on the distinctive feature of LSV in Co 3+ and Co 4+ ‐mediated range, it can therefore be concluded that the RDS for Co 4+ ‐mediated HMF oxidation is the electrochemical regeneration of catalytically active Co 4+ species [6] …”
Section: Resultsmentioning
confidence: 97%
“…While in the case of Co 4+ , the oxidation current quickly increases after the onset of Co 4+ formation, suggesting the consumption rate of Co 4+ well surpasses its generation rate and therefore increasing quantity of M 4+ is generated and participating in the HMF oxidation. Based on the distinctive feature of LSV in Co 3+ and Co 4+ ‐mediated range, it can therefore be concluded that the RDS for Co 4+ ‐mediated HMF oxidation is the electrochemical regeneration of catalytically active Co 4+ species [6] …”
Section: Resultsmentioning
confidence: 97%
“…In previously reported HMF oxidation catalyzed by Ni-based electrocatalyst, the Ni 3+ / Ni 2+ redox couple shows no selectivity towards the oxidation of hydroxyl and formyl groups,therefore producing FDCA as the dominant product. [6,19] To emphasize the oxidation-state dependent selectivity of electrogenerated Co species,b enchmark NiO x H y electrode was prepared following the same electrodeposition protocol and product selectivity towards HMF oxidation was examined under various applied potentials (1.4 V, 1.45 Vand 1.5 Vvs. RHE).…”
Section: Angewandte Chemiementioning
confidence: 99%
“…1i). 20 Therefore, it is of great signi cance for catalysts to have the optimal OHand organic adsorption capability. The DFT calculation was conducted to con rm the vital role of Vo in HMFOR.…”
Section: The Electrochemical Performance Ofmentioning
confidence: 99%
“…15,16,17 OH ad is the crucial intermediate for the oxygen evolution reaction (OER) and alcohol molecules catalytic cycle, which has been widely recognized the reaction mechanism. 18,19,20 In ethanol oxidation, the H* derived from the dehydrogenation of hydroxyl groups is combined with OH ad in the alkaline solution. 20,21 Since the HMFOR process includes the oxidation of hydroxyl and aldehyde groups, different adsorption energies and sites of OHon catalysts signi cantly in uence the HMFOR activity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation